The influence of factor V Leiden and G20210A prothrombin mutation on the presence of residual vein obstruction after idiopathic deep-vein thrombosis of the lower limbs - Cosmi, Benilde; Legnani, Cristina; Pengo, Vittorio; Ghirarduzzi, Angelo; Testa, Sophie; Poli, Daniela; Prisco, Domenico; Tripodi, Armando; Palareti, Gualtiero; for the PROLONG Investigators FCSA, Italian Federation of Anticoagulation Clinics; on behalf of (Thrombosis and Haemostasis, 2013)
It was our aim to assess whether factor V Leiden (FVL) and G20210A prothrombin (FII) mutation are associated with the presence of residual vein obstruction (RVO) after a standard course of anticoagulation for a first episode of idiopathic proximal deep-vein thrombosis (DVT) of the lower limbs, with or without symptomatic pulmonary embolism (PE). Patients were enrolled in two prospective multicentre studies: PROLONG and PROLONG II. RVO was detected by compression ultra-sonography according to the method of Prandoni on the day of anticoagulation withdrawal. Patients were also screened for FVL and FII mutation. The presence of FVL and/or FII mutation was determined in 872/963 (90.5%) patients, in 753 of whom RVO was assessed. FVL was significantly less frequent among subjects with isolated PE (7/176:4%) than among patients with either DVT and PE (15/133:11.3%; p=0.0018) or isolated DVT (89/563:15.8%; p<0.0001), confirming the FVL paradox. The rate of FII mutation was similar among patients with isolated PE (11/176:6.2%) and patients with either DVT and PE (12/133:9%) or isolated DVT (52/563:9.2%). FVL and FII mutation were not significantly associated with RVO at the multivariate analysis in all patients, although data suggest that FVL and FII mutation may have a differential effect on RVO in the subgroups of patients with DVT and DVT plus PE patients. Male sex and isolated DVT were significantly associated with RVO in all patients. In conclusion, male sex and isolated DVT are associated with RVO, while FVL and FII mutations are not significantly associated with RVO in this study.
Keywords: Deep-vein thrombosis; pulmonary embolism; thrombophilia; venous thrombosis; residual vein obstruction